Extent and consequences of lymphadenectomy in oesophageal cancer surgery: case vignette survey. Issue 1 (2nd April 2020) - de Gouw, Didi JJM; Scholte, Mirre; Gisbertz, Suzanne S; Wijnhoven, Bas P L; Rovers, Maroeska M; Klarenbeek, Bastiaan R; Rosman, Camiel
Abstract : Objectives: Lymph node dissection (LND) is part of the standard operating procedure in patients with resectable oesophageal cancer after neoadjuvant chemoradiotherapy regardless of lymph node (LN) status. The aims of this case vignette survey were to acquire expert opinions on the current practice of LND and to determine potential consequences of non-invasive LN staging on the extent of LND and postoperative morbidity. Design: An online survey including five short clinical cases (case vignettes) was sent to 272 oesophageal surgeons worldwide. Participants: 86 oesophageal surgeons (median experience in oesophageal surgery of 15 years) participated in the survey (response rate 32%). Main outcome measures: Extent of standard LND, potential changes in LND based on accurate LN staging and consequences for postoperative morbidity were evaluated. Results: Standard LND varied considerably between experts; for example, pulmonary ligament, splenic artery, aortopulmonary window and paratracheal LNs are routinely dissected in less than 60%. The omission of (parts of) LND is expected to decrease the number of chyle leakages, pneumonias, and laryngeal nerve pareses and to reduce operating time. In order to guide surgical treatment decisions, a diagnostic test for LN staging after neoadjuvant therapy requires a minimum sensitivity of 92% and a specificity of 90%. Conclusions: This expert case vignette survey study shows that there is no consensus on the extent of standard LND. Oesophageal surgeons seem more willing to extend LND rather than omit LND, based on accurate LN staging. The majority of surgeons expect that less extensive LND can reduce postoperative morbidity.